Catalisadores Cu-, Co- ou Fe-ZSM-5 caracterização e avaliação na redução de NO a N2 com hidrocarbonetos na presença ou ausência de vapor de água - Fernandes, Juliana Esteves (Universidade Federal de São Carlos, 2005)
The minimization of the emissions of nitrogen oxides (NOx) in the atmosphere has been one of the great goals in the area of environmental protection. Among the possible processes to treat the NOx, the selective catalytic reduction of NO with hydrocarbons (SCR-HC) has presented important expectations. For this process, the metal/ZSM-5 type catalysts have appropriate levels of conversion in oxidative conditions. In this context, the aim of this work was to prepare Cu, Co and FeZSM-5 catalysts. The samples were characterized by XRD, DRS-UVVIS, FTIR, H2-TPR, SEM and tested in the reduction of NO to N2 with propane or methane in oxidative atmosphere in the presence or absence of water steam. The H2-TPR data showed that the cationic species present in the prepared Cu, Co and FeZSM-5 catalysts, after thermal activation, were mainly Cu2+ (Cuα 2+ e Cuβ 2+), Co2+ and Fe3+ cations located in charge compensation sites in the zeolite, respectively. From FTIR and DRS-UVVIS it was also possible identify oxide species, which were present in a lower content. In the reduction of NO to N2 in the absence of water steam, the CuZSM-5 catalysts showed higher levels of conversion of NO than those based in Co and Fe. However, the FeZSM-5 catalysts showed, in this condition, activity at lower temperatures. This behavior makes them potentially interesting to be applied for practical purposes. On the other hand, in the presence of water steam, it was verified a higher loss of activity of the CuZSM-5 catalyst, which was totally restored removing the water in the feed. For the Co and FeZSM-5 catalysts, the activity loss in the presence of water steam was partially recovered during time on stream.
Keywords: Catalisadores; Redução de NO; Catalisador Cu/ZSM-5; Catalisador Fe/ZSM-5; Catalisador Co/ZSM-5; ENGENHARIAS::ENGENHARIA QUIMICA